A novel approach to risk assessment for occupational health and safety using Pythagorean fuzzy AHP & fuzzy inference system - Ilbahar, Esra; Karasan, Ali; Cebi, Selcuk; Kahraman, Cengiz (ELSEVIER SCIENCE BV, 2018)
Occupational health and safety involves systematic studies aimed at protecting employees from harmful conditions that might be caused by various reasons during the execution of work in the workplace. Different from the literature, in this study, a novel integrated approach, Pythagorean Fuzzy Proportional Risk Assessment (PFPRA), including Fine Kinney, Pythagorean fuzzy analytic hierarchy process, and a fuzzy inference system is used for risk assessment in the field of occupational health and safety. The main difference of the proposed approach is the integration of these methods in a way providing a more accurate risk assessment. The risks of an excavation process in a construction yard are assessed by the proposed method. The results are compared with Pythagorean Fuzzy Failure Modes and Effects Analysis (PFFMEA) and it is revealed that the proposed method produces reliable and informative outcomes better representing the vagueness of decision making process.
Keywords: Pythagorean fuzzy sets; AHP; Fuzzy inference system; FMEA; Fine Kinney; ANALYTIC HIERARCHY PROCESS; MANAGEMENT-SYSTEM; DECISION-MAKING; SETS; METHODOLOGIES; INDICATORS; ACCIDENTS; SHIPYARDS; SELECTION; TOPSIS; Engineering; Operations Research & Management Science